2019
DOI: 10.1002/cbic.201900512
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Cellular Uptake of RGD Peptides

Abstract: Monomeric RGD peptides show unspecific fluid‐phase uptake in cells, whereas multimeric RGD peptides are thought to be internalized by integrin‐mediated endocytosis. However, a potential correlation between uptake mechanism and molecular mass has been neglected so far. A dual derivatization of peptide c(RGDw(7Br)K) was performed to investigate this. A fluorescent probe was installed by chemoselective Suzuki–Miyaura cross‐coupling of the 7‐bromotryptophan and a poly(ethylene glycol) (PEG) linker was attached to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Low TI values may also be associated with non-receptor-mediated uptake mechanisms. The size-dependent cellular uptake ( Kemker et al, 2019 ) could be an explanation for this behavior because of the relatively low molecular mass of the conjugates 16-18 . It was also previously reported that a integrin α V β 3 -addressing cRGDfK-carboxyfluorescein conjugate was taken up by integrin-positive and integrin-negative cell lines with the assumption of a fluid-phase uptake ( Borbély et al, 2019a ).…”
Section: Resultsmentioning
confidence: 99%
“…Low TI values may also be associated with non-receptor-mediated uptake mechanisms. The size-dependent cellular uptake ( Kemker et al, 2019 ) could be an explanation for this behavior because of the relatively low molecular mass of the conjugates 16-18 . It was also previously reported that a integrin α V β 3 -addressing cRGDfK-carboxyfluorescein conjugate was taken up by integrin-positive and integrin-negative cell lines with the assumption of a fluid-phase uptake ( Borbély et al, 2019a ).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for this result is the involvement of internalization. 27 Once the radioligand-receptor complex is internalized into cells, the dissociation kinetics of radioactivity from the cells would be completely different. Although we did not investigate the degree of internalization in this study, the influence of linker molecules on the internalization process is worth investigating and the subject of our future study.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Besides addressing the indole C 2 , the regioselective enzymatic halogenation at C5, C6, or C7 using FAD-dependent tryptophan halogenases opens a broad area of Pd-catalysed late-stage diversifications [53][54][55]. It has been proven that Pd-catalysed cross-couplings are very versatile tools for selective and bio-orthogonal modifications of haloindoles, halotryptophans and halotryptophan-containing peptides as well as natural products [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Additionally, halotryptophans were incorporated in pentapeptides as building blocks for macrocyclisation by Suzuki-Miyaura cross-coupling (SMC) aiming at the preparation of bicyclic peptides [71].…”
Section: Introductionmentioning
confidence: 99%